The Oxford handbook of the Ancien Régime - Doyle, William 1942- (Oxford handbooks, 2012)
Machine generated contents note: 1.Introduction / William Doyle -- pt. I GOVERNMENT -- 2.Absolute Monarchy / Peter R. Campbell -- 3.Diplomacy / Hamish Scott -- 4.Armed Forces / David Parrott -- 5.Finances / Joel Felix -- 6.Parlements and Provincial Estates / Julian Swann -- pt. II SOCIETY -- 7.Nobility / John Shovlin -- 8.Bourgeoisie / Sarah Maza -- 9.Estates, Orders, and Corps / Gail Bossenga -- 10.Poverty / Alan Forrest -- 11.Gender / Julie Hardwick -- pt. III ECONOMY -- 12.Demography / Jack A. Goldstone -- 13.Feudalism / Anthony Crubaugh -- 14.Agriculture / Peter M. Jones -- 15.Commerce / Silvia Marzagalli -- 16.Slavery and Serfdom / William Doyle -- pt. IV RELIGION -- 17.The Established Church / Nigel Aston -- 18.Popular Religion / Robin Briggs -- 19.Jansenism / Thomas O'Connor -- 20.Dissent and Toleration / Marisa Linton -- pt. V CULTURE -- 21.Education / Dorinda Outram -- 22.Sociability / Pierre-Yves Beaurepaire -- 23.Patronage / Mark Ledbury -- 24.The Public Sphere / Thomas E. Kaiser -- pt. VI SOLVENTS? -- 25.Enlightenment / Thomas Munck -- 26.Technological Change / Alessandro Nuvolari -- 27.Revolution / Michael Rapport -- pt. VII TEST CASES -- 28.The Napoleonic Regimes / Michael Broers -- 29.Reformed and Unreformed Britain, 1689-1801 / Julian Hoppit -- 30.Colonial America / Christopher Clark -- 31.The Old Reich / Peter H. Wilson -- 32.Conclusion / William Doyle